The effect of a field-based warm-up on performance in BMX cycling - Rylands, L. P.; Mitchell, J.; Taylor, N.; Hurst, H. (Journal of Science and Cycling, 2025)
Performing a warm-up in sport is generally seen as an essential part of any pre-race routine. However, studies have reported mixed findings on the benefits of such routines and few studies have looked at the influence of warm-up on BMX performance. Therefore, this study aimed to 1) ascertain if a warm-up had an effect on BMX performance 2) whether a rest period post warm-up affected performance, and 3) if a sub-maximal warm-up could influence performance to a greater extent. The study assessed 11 competitive BMX riders in a field-based environment on an indoor BMX track. Riders performed three trials. In trial one, they performed a maximal effort lap on the track without a warm-up. In trial two, riders performed a conventional warm-up, generally consisting of sprint intervals, then sat for 10-minutes in a holding area before performing another timed sprint lap. Lastly, for trial three, rider performed a structed sub-maximal warm-up then performed a final maximal effort sprint on the track. The results found no statistical differences between the trials (F(2,30)= .18; p >=.05; Eta2=.01). However, there was a difference in mean times when comparing trial 2 (34.1 ± 3.70 s) and 3 (34.2 ± 3.70 s) to the non-warm up trial (34.9 ± 3.58 s). The time differences may appear marginal, but when applied to race data they could have a potential impact. Research has shown that 0.49 ± 0.36 s faster lap times can result in a rider moving up at least one position or progressing to the next round in the heats.